The Influence Of Price Perception And Service Quality On Purchasing Decisions At Tansoe Nature Coffee Tasikmalaya - Rizky Maulana; Depy Muhamad Pauzy (Journal of Indonesian Management, 2022)
This study aims to determine the Influence of Price Perception and Service Quality on purchasing decisions at Tansoe Nature Coffee. The research method uses quantitative methods with a survey approach, the survey in this study to Tansoe Nature Coffee consumers with a sample of 100 consumers. The data used is primary and secondary data. The data analysis technique that is used is Multiple Linear Regression Analysis using SPSS Software v.25. The results of hypothesis testing research show that Price Perception and Service Quality have a Significant Effect on Purchasing Decisions at Tansoe Nature Coffee simultaneously Price Perception and Service Quality have a significant influence on Purchasing Decisions. Partially Price Perception has a significant influence on Purchasing Decisions. Partially, the Quality of Service has a significant effect on purchasing decisions.